2013
DOI: 10.1186/1756-8722-6-4
|View full text |Cite
|
Sign up to set email alerts
|

Intensity modulated radiotherapy for sinonasal malignancies with a focus on optic pathway preservation

Abstract: PurposeTo assess if intensity-modulated radiotherapy (IMRT) can possibly lead to improved local control and lower incidence of vision impairment/blindness in comparison to non-IMRT techniques when treating sinonasal malignancies; what is the most optimal dose constraints for the optic pathway; and the impact of different IMRT strategies on optic pathway sparing in this setting.Methods and materialsA literature search in the PubMed databases was conducted in July, 2012.ResultsClinical studies on IMRT and 2D/3D … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 47 publications
3
14
0
Order By: Relevance
“…63,64 It is useful in reducing long-term toxicity in H&N cancers and particularly NPC by reducing the dose to ≥1 major salivary glands, temporal lobes, mandible, auditory structures (including the cochlea), and optic structures. [65][66][67][68][69] IMRT may help to preserve the optic pathway in patients with sinonasal malignancies. 65 A prospective Korean study showed that 3-dimensional and IMRT techniques were superior to 2-dimensional radiation for both PFS and OS, and IMRT was associated with improved survival in multivariate analysis, particularly in T3-T4 tumors.…”
Section: Radiation Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…63,64 It is useful in reducing long-term toxicity in H&N cancers and particularly NPC by reducing the dose to ≥1 major salivary glands, temporal lobes, mandible, auditory structures (including the cochlea), and optic structures. [65][66][67][68][69] IMRT may help to preserve the optic pathway in patients with sinonasal malignancies. 65 A prospective Korean study showed that 3-dimensional and IMRT techniques were superior to 2-dimensional radiation for both PFS and OS, and IMRT was associated with improved survival in multivariate analysis, particularly in T3-T4 tumors.…”
Section: Radiation Therapymentioning
confidence: 99%
“…[65][66][67][68][69] IMRT may help to preserve the optic pathway in patients with sinonasal malignancies. 65 A prospective Korean study showed that 3-dimensional and IMRT techniques were superior to 2-dimensional radiation for both PFS and OS, and IMRT was associated with improved survival in multivariate analysis, particularly in T3-T4 tumors. 70 Proton therapy has also been used to treat sinonasal malignancies.…”
Section: Radiation Therapymentioning
confidence: 99%
“…11 IMRT has been shown to reduce longterm toxicity in oropharyngeal, paranasal, and nasopharyngeal cancers without any compromise in overall survival. [12][13][14][15][16][17] NCCN guidelines currently state a preference for the use of either IMRT or 3D conformal RT for treatment of all head and neck subsites, with IMRT preferred for paranasal and nasopharyngeal cancers. Methods of delivering IMRT include the simultaneous integrated boost (SIB) and sequential (SEQ) technique.…”
Section: General Principlesmentioning
confidence: 99%
“…IMRT involves the modulation of radiation beams to reduce doses to normal structures while still delivering effective doses to target sites, utilizing computer‐based inverse planning . IMRT has been shown to reduce long‐term toxicity in oropharyngeal, paranasal, and nasopharyngeal cancers without any compromise in overall survival . NCCN guidelines currently state a preference for the use of either IMRT or 3D conformal RT for treatment of all head and neck subsites, with IMRT preferred for paranasal and nasopharyngeal cancers.…”
Section: Introductionmentioning
confidence: 99%
“…In this disease, intensity-modulated radiotherapy decreased long-term toxicity with no negative eff ect on overall survival when compared with 3D-conformal radiotherapy. [54][55][56][57][58][59][60][61][62][63][64][65][66] Stereotactic ablative radiotherapy is a novel radiotherapy method that delivers a very high dose of radiation (in a single or a few fractions) with high precision to the tumour, thus maximising the sparing of surrounding normal tissue. Several retrospective and prospective stereotactic ablative radiotherapy studies have shown promising results in terms of local tumour control and survival in some settings, including in early non-small-cell lung cancer.…”
Section: Clinical Solutions and Future Perspectivesmentioning
confidence: 99%